PENGARUH KOMBINASI MALTODEKSTRIN-KITOSAN PADA EDIBLE COATING UNTUK MEMPERTAHANKAN KUALITAS BUAH APEL POTONG - Aqila Yulinda Sani; Puti Naomi Mazaya; Ayu Pita Kurniasari; Hermawan Dwi Ariyanto (Fakultas Teknik Universitas Wahid Hasyim, 2025)
The browning of freshly sliced apples greatly diminishes their quality and attractiveness to consumers. Edible coatings offer a viable solution for maintaining the quality and prolonging the shelf life of cut fruit. This research examined the impact of combining maltodextrin and chitosan in edible coatings on the quality of fresh-cut apples. The dip-coating technique was utilized to apply the coating. A Completely Randomized Design (CRD) with two factors was used, featuring various maltodextrin (MD)-to-chitosan weight ratios (1:1, 1:3, and 3:1) and two types of maltodextrin with different dextrose equivalent (DE) values (10 and 25). The performance of the edible coatings was assessed over a 10-day storage period at 4°C, with evaluations conducted on days 0, 2, 4, 6, 8, and 10. The findings indicated that the optimal preservation of apple quality was achieved with a 3:1 MD-to-chitosan ratio combined with DE 25, resulting in a browning index of 36.09, firmness measuring 5.7 kg/cm², vitamin C content of 20.43 mg/100 g, and a weight loss of 18.09%. In terms of organoleptic assessment (rated on a 1–5 scale), samples with the same MD-to-chitosan ratio received the highest ratings for color (2.65) and texture (2.5). The treatment with a 3:1 MD-to-chitosan ratio and DE 10 yielded the best aroma score of 2.3.